(untitled) (The Pakistan Development Review, 1995)
This is a micro study of the growth and distribution of the non-land agrarian assets in the Punjab between 1970 and 1984. This period of farm accumulation is interesting especially since it allows us to trace the agricultllral productivity impact of the Green Revolution (introduced in the late 1960’s) on the distribution of wealth. The Green Revolution was based on a wide spread adoption of inputs, HYV seed, and fertiliser, albeit with some evidence of time lags and differentials across farm size, and it generated a high rate of acquisition of agrarian assets, especially tubewells and mechanisation. The introduction of the HYV inputs definitely enhanced profitability, income, and wealth in the farm sector, but its impact on the distribution of agrarian assets across income classes was not so definite. This study focuses on this less well-researched aspect of the distribution of wealth generated by the Green Revolution. To examine asset accumulation. we posit an analytical framework of exogenous and endogenous constraints on growth, which is useful in picking up both the common and contrasting patterns of growth and distribution across the two distinct regions of the Punjab. the canal colonies. and southern Punjab. The first exogenous constraint of an imperfect credit market is macro in nature. and is common to both regions. which strongly handicaps asset acquisition by small farmers. Further. there is evidence that, given the new technology. the ownership of assets is an important determinant of both growth and distribution. So this initial equity bias against small farmers in the first round of accumulation implies an even greater bias in the second round. The second endogenous constraint is regionally specific to the more land-concentrated southern region. which generates supervision costs for the largest operators. preventing them from expanding their operated area further through increased mechanisation. It also adds to the persistence in southern Punjab of the contractual form of sharecropping, in contrast to the proliferation of self-cultivation and use of wage-labour in the canal colonies.